2012
DOI: 10.1039/c2sm06744g
|View full text |Cite
|
Sign up to set email alerts
|

Drop impacts on electrospun nanofiber membranes

Abstract: This work reports a systematic study of drop impacts of polar and non-polar liquids onto different electrospun nanofiber membranes (of 8-10 mm thickness and pore sizes of 3-6 mm) with an increasing degree of hydrophobicity. The liquids studied were water, FC 7500 (Fluorinert fluid) and hexane. The nanofibers used were electrospun from polyacrylonitrile (PAN), nylon 6/6, polycaprolactone (PCL) and Teflon. It was found that for any liquid/fiber pair there exists a threshold impact velocity ($1.5 to 3 m s À1 ) ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 29 publications
(66 reference statements)
2
60
0
Order By: Relevance
“…This means that the pores hardly impose a significant hydraulic resistance. Nevertheless, due to a relatively high surface tension of blood (σ = 60.45 g/s 2 ), individual blood jets issued from the pores will immediately merge and form an intact layer, as observed in the experiments with high surface tension liquids in [38]. In distinction from [38], this intact liquid layer is subjected to tremendously high acceleration toward air and thus is prone to the Rayleigh-Taylor instability which sets an ultimate drop size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the pores hardly impose a significant hydraulic resistance. Nevertheless, due to a relatively high surface tension of blood (σ = 60.45 g/s 2 ), individual blood jets issued from the pores will immediately merge and form an intact layer, as observed in the experiments with high surface tension liquids in [38]. In distinction from [38], this intact liquid layer is subjected to tremendously high acceleration toward air and thus is prone to the Rayleigh-Taylor instability which sets an ultimate drop size.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, due to a relatively high surface tension of blood (σ = 60.45 g/s 2 ), individual blood jets issued from the pores will immediately merge and form an intact layer, as observed in the experiments with high surface tension liquids in [38]. In distinction from [38], this intact liquid layer is subjected to tremendously high acceleration toward air and thus is prone to the Rayleigh-Taylor instability which sets an ultimate drop size. Note also that when a target sponge is covered by tape or silicone (not the case in the present work), the blood spatter can be affected causing an uneven distribution of drops [19].…”
Section: Resultsmentioning
confidence: 99%
“…Very low adhesion values were obtained in the case of coatings consisting of viscoelastic elastomers. Yarin and co‐workers reported a systematic study of drop impacts of polar and nonpolar liquids onto different electrospun nanofiber membranes with an increasing degree of hydrophobicity. It is found that for any liquid/fiber pair there exists a threshold impact velocity (≈1.5–3 m s −1 ) above which water penetrates membranes irrespective of their hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…A requirement for this behaviour is that the solid surface be chemically heterogeneous so as to allow different distributions of chemical functional groups between those that are on the surface and those buried deeper in it. This effect is associated with a variety of phenomena including the marked differences between chemisorbed and physisorbed monolayers 7 and wetting transitions 8 with implications ranging from plant growth 9 through electrovariable optical components 10 to nanofiber membranes 11 , which are chemically heterogeneous.…”
mentioning
confidence: 99%